Prevalence and Clinical Relevance of Extracardiac Findings in Cardiovascular Magnetic Resonance Imaging. Issue 1 (January 2019) - Mantini, Cesare; Mastrodicasa, Domenico; Bianco, Francesco; Bucciarelli, Valentina; Scarano, Michele; Mannetta, Gianluca; Gabrielli, Daniela; Gallina, Sabina; Petersen, Steffen E.; Ricci, Fabrizio; Cademartiri, Filippo
Abstract : Purpose: To assess the prevalence of extracardiac findings (ECF) during cardiovascular magnetic resonance (CMR) examinations and their downstream effect on clinical management. Materials and Methods: We retrospectively identified 500 consecutive patients. Trans-axial balanced steady-state free precession nongated images acquired from the upper thorax to the upper abdomen were evaluated independently by 2 radiologists. ECF were classified as nonsignificant (benign, with no need for further investigation), significant (mandatory to be reported/monitored), and major (clinically remarkable pathology, mandatory to be reported/investigated/treated). Fifteen-month clinical follow-up information was collected through hospital records. Results: Of 500 patients, 108 (21.6%) showed a total of 153 ECF: 59 (11.8% of the entire study population; 38.5% of all ECF) nonsignificant, 76 (15.2%; 49.7%) significant, and 18 (3.6%; 11.8%) major ECF. The most frequent ECF were pleural effusion, hepatic cyst, renal cyst, and ascending aorta dilatation. Of 94 significant and major ECF, 46 were previously unknown and more common in older patients. Newly diagnosed major ECF (n=11, 2.2% of the entire study population, and 7.2% of all ECF)—including 5 tumors (1% of study population)—were confirmed by downstream evaluations and required specific treatment. Patients with major ECF were significantly older than patients without with major ECF. Newly diagnosed clinically significant and major ECF prompted downstream diagnostic tests in 44% and 100% of cases, respectively. Conclusions: The detection of significant and major ECF is common during CMR reporting. The knowledge and the correct identification of most frequent ECF enable earlier diagnoses and faster treatment initiation of unknown extracardiac pathologies in patients referred to CMR imaging.